Biomimetic design of building facades: an evolutionary-based computational approach inspired by elephant skin for cooling in hot and humid climates - Hays, Nathan; Badarnah, Lidia; Jain, Anuj (Frontiers in Built Environment, 2024)
The built environment faces significant challenges in managing energy demands amidst rising temperatures and increasing concerns linked to climate change. Meeting carbon emissions targets and resource management goals necessitates urgent innovation in more energy-efficient cooling solutions. Nature offers a large database of adaptive and efficient thermal solutions that can be harnessed through biomimetic methods in building design and systems. Emerging biomimetic and computational approaches hold promise in facilitating practical application efforts. This paper investigates the translation of morphological features from elephant skin to building facades, optimizing their inherent cooling capabilities through computational design using evolutionary algorithms. Through this exploration, we propose a set of generalized evolutionary principles, offering a foundational framework for the development of textured facade tiles with the aim of mitigating heat gain from solar radiation. This study provides an in-depth analysis of how assembly, texture depth, and orientation impact thermal performance, enabling the design of more effective passive cooling systems through an understanding of the relationship between morphological variations in textured surfaces and environmental performance. Future research may involve studying natural convection dynamics, optimizing capillary networks, evaluating materials for water adhesion and cleaning, assessing impacts on biological growth, and exploring biodiversity integration within textured facade panels.